Harmonization in A Multicultural Society in Padangpanjang City - Wulandari, Putri Wiyani; Endrizal (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research examines "Harmonization in a multicultural society in Padangpanjang city". The purpose of this research is to see what values the community holds firmly in order to harmonize the harmonization. The writing method used by the presenter is a qualitative method. The theory of multiculturalism becomes a dissection of the problems used by the presenter. The findings of this study indicate that the harmonization of religious communities in the middle of the city of Padangpanjang is still maintained despite the pressure of the Islamic majority.